2012
DOI: 10.1371/journal.pone.0041323
|View full text |Cite
|
Sign up to set email alerts
|

The Redder the Better: Wing Color Predicts Flight Performance in Monarch Butterflies

Abstract: The distinctive orange and black wings of monarchs (Danaus plexippus) have long been known to advertise their bitter taste and toxicity to potential predators. Recent work also showed that both the orange and black coloration of this species can vary in response to individual-level and environmental factors. Here we examine the relationship between wing color and flight performance in captive-reared monarchs using a tethered flight mill apparatus to quantify butterfly flight speed, duration and distance. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
70
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 27 publications
(41 reference statements)
3
70
0
Order By: Relevance
“…Coloration is usually closely tied to fitness because it plays important roles in mate choice (Graham et al 1980, Endler & Houde 1995, Summers et al 1999, Maan et al 2004, Maan & Cummings 2008, Estrada & Jiggins 2008, thermoregulation (Tsuji et al 1986, Guppy 1986b, Davis et al 2012, and protection from predators (Wallace 1879, Endler 1983. Therefore, the study of color and how animals use coloration is necessary to fully understand the natural history, ecology, and evolution of any organism (Fogden & Fogden 1974).…”
Section: Biological Significance Of Colorationmentioning
confidence: 99%
See 1 more Smart Citation
“…Coloration is usually closely tied to fitness because it plays important roles in mate choice (Graham et al 1980, Endler & Houde 1995, Summers et al 1999, Maan et al 2004, Maan & Cummings 2008, Estrada & Jiggins 2008, thermoregulation (Tsuji et al 1986, Guppy 1986b, Davis et al 2012, and protection from predators (Wallace 1879, Endler 1983. Therefore, the study of color and how animals use coloration is necessary to fully understand the natural history, ecology, and evolution of any organism (Fogden & Fogden 1974).…”
Section: Biological Significance Of Colorationmentioning
confidence: 99%
“…Some of the species found to have geographically varying warning signals include Neotropical Heliconius butterflies (Brown & Benson 1974, Brower 1996, Mallet 2010, ladybird beetles (Creed 1966, Brakefield 1985, DolenskĂĄ et al 2009, Blount et al 2012, monarch butterflies (Brower 1958, Davis et al 2005, Davis et al 2012, newts (Mochida 2009, Mochida 2011, poison frogs (Daly & Myers 1967, Savage 1968, Summers et al 2003, Wang & Summers 2010, Wang 2011, Rudh et al 2011, Maan & Cummings 2012, Willink et al 2013, RichardsZawacki et al 2013, Hegna et al 2013b), velvet ants (Wilson et al 2012), alpine leaf beetles (Borer et al 2010), and bumble bees (Plowright & Owen 1980). Interestingly, some aposematic species appear to switch between aposematic and cryptic strategies across their distributions.…”
Section: Geographic Variation For Different Preymentioning
confidence: 99%
“…In addition to isotopic signature, there is also evidence that intraspecific variation in the movement behaviors of monarch butterflies may be correlated with measurable variation in several other aspects of the butterfly phenotype (Altizer et al , Dockx , Altizer and Davis , Davis et al , Zhan et al ). In particular, previous studies have suggested that monarch butterflies from different populations show variation in wing morphology which is correlated with their migratory behavior (Beall and Williams , Dockx , , Altizer and Davis ).…”
mentioning
confidence: 99%
“…Conducting the pulling trials over time also allowed the monitoring of evidence of fatigue, which has been seen in other studies of insect locomotion (e.g., Herreid et al 1981; Harrison et al 1991; Davis et al 2012). Interestingly, there was no consistent pattern of reduced force over time in the data.…”
Section: Discussionmentioning
confidence: 99%